The Estimation of Multidimensional Fixed Effects Panel Data Models - Balazsi, Laszlo; Matyas, L.; Wansbeek, T. (Taylor and Francis, 2015)
This article introduces the appropriate within estimators for the most frequently used three-dimensional fixed effects panel data models. It analyzes the behavior of these estimators in the cases of no self-flow data, unbalanced data, and dynamic autoregressive models. The main results are then generalized for higher dimensional panel data sets as well.